2021
DOI: 10.1002/csr.2180
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting volatility by integrating financial risk with environmental, social, and governance risk

Abstract: The study aims to verify whether the consideration of a risk measure based on environmental, social, and governance (ESG) factors can reduce the difference between the ex‐ante financial risk and ex‐post volatility of financial assets. The statistical models are run on 17,996 firm‐year observations (3332 active firms from 55 countries and 10 industries, listed on the ECPI Global Ethical Equity index) in 2007–2015. According to our main results, the forecasting effectiveness of traditional financial risk measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 110 publications
0
22
0
Order By: Relevance
“…Two main beneficiaries of corporate social responsibility amid the pandemic and crisis changed their priorities. Employees (the first beneficiary) are interested not just in preserving their jobs but in their professional activities' becoming safe (from the positions of observing sanitary and epidemiological norms) (Capelli et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two main beneficiaries of corporate social responsibility amid the pandemic and crisis changed their priorities. Employees (the first beneficiary) are interested not just in preserving their jobs but in their professional activities' becoming safe (from the positions of observing sanitary and epidemiological norms) (Capelli et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent scientific papers, the relationship between CSR and risk has deepened in terms of reworking traditional risk management models. For example, Capelli et al (2021) argue that CSR risk analysis can improve financial risk assessment by integrating traditional risk management models with entropy analysis related to ESGs. This conclusion is consistent with the general idea that VaR (Value at Risk) models should be continually revised because of the arising of new independent variables that affect the volatility of stock prices (Bloomberg, 2011; Berkowitz and O'Brien, 2002).…”
Section: Prior Literaturementioning
confidence: 99%
“…Studies have revealed that integrating ESG into a company's strategy improves not only financial performance (Brogi & Lagasio, 2019; Ellili & Nobanee, 2022; Gallego‐Álvarez & Pucheta‐Martínez, 2021; La Torre et al, 2021), market value (Aureli et al, 2020; Lo & Kwan, 2017), and investment efficiency (Ellili, 2022; Harymawan et al, 2022) but also forecasts the effectiveness of financial asset volatility (Capelli et al, 2021), and mitigates the cost of capital (Raimo et al, 2021). In addition, this integration enhances other non‐financial indicators, such as reputation (Karwowski & Raulinajtys‐Grzybek, 2021; Murè et al, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%